2016
DOI: 10.1093/toxsci/kfw227
|View full text |Cite
|
Sign up to set email alerts
|

From the Cover: High-Throughput Imaging of Cardiac Microtissues for the Assessment of Cardiac Contraction during Drug Discovery

Abstract: Cardiotoxicity is a common cause of attrition in preclinical and clinical drug development. Current in vitro approaches have two main limitations, they either are limited to low throughput methods not amendable to drug discovery or lack the physiological responses to allow an integrated risk assessment. A human 3D cardiac microtissue containing human-induced pluripotent stem cell-derived cardiomyocytes (hiPS-CMs), cardiac endothelial cells and cardiac fibroblast were used to assess their suitability to detect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 49 publications
1
44
0
Order By: Relevance
“…This is the first study reporting the use of a large, diverse panel of different structural cardiotoxin drug classes in combination with an advanced cardiac in vitro model assessing cardiac structure. Studies to date in advanced cardiac models have assessed cardiac function, primarily profiling a small number of compounds 35 , 39 , 40 or specific functional acute alterations 41 . Our data suggests that the combination of imaging parameters and assessment of cellular viability in cardiac microtissues can predict the in vivo outcome of structural cardiotoxins (change in cardiac morphology or clinical biomarker release) with an overall sensitivity of 73% and specificity of 86%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the first study reporting the use of a large, diverse panel of different structural cardiotoxin drug classes in combination with an advanced cardiac in vitro model assessing cardiac structure. Studies to date in advanced cardiac models have assessed cardiac function, primarily profiling a small number of compounds 35 , 39 , 40 or specific functional acute alterations 41 . Our data suggests that the combination of imaging parameters and assessment of cellular viability in cardiac microtissues can predict the in vivo outcome of structural cardiotoxins (change in cardiac morphology or clinical biomarker release) with an overall sensitivity of 73% and specificity of 86%.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies investigating structural cardiotoxicity identified the importance of the use of an in vitro model that was actively contracting 18 . As these cardiac microtissues have a higher spontaneous beat rate 41 , it could also be hypothesized that the increased contraction, and thus energy utilization, increases the sensitivity to perturbations and that small modifications in the cellular ATP pool could potentially have a greater impact on cellular health in cells with a higher basal beat rate.…”
Section: Discussionmentioning
confidence: 99%
“…While the concept of examining multiple parameters from waveforms has been pursued lately, some studies have suggested that only a few select parameters (e.g., peak count) are necessary in assessing a compound's cardioactivity as other parameters provide no further mechanistic insight ( Lu et al., 2015 , Pointon et al., 2016 , Sirenko et al., 2013 ). This is primarily true when the hPSC-CMs are spontaneously beating, meaning the force generated is linked to beating frequency.…”
Section: Resultsmentioning
confidence: 99%
“…Several labs have deployed advanced video microscopy analyses of drug‐induced changes in contractile function of hiPSC‐CMs, from single cells to 3D tissue constructs. [ 91,98,108,114–116 ] Common mechanical readouts include changes in peak contraction/relaxation amplitudes, contraction/relaxation velocities, and beat rate (Table 2). For example, Sala et al deployed their “MUSCLEMOTION” analysis software to study the cardiotoxic agent Nifedipine (a Ca 2+ channel blocker used to treat hypertension) and learn that it reduces contraction amplitudes in single‐cell hiPSC‐CM, hiPSC‐CM monolayers, and 3D tissue constructs.…”
Section: Assays Used In Cardiotoxicity Studies To Measure Active Forcementioning
confidence: 99%